Distributive differences of P2Xs between the forelimb and hind limb of adjuvant arthritis rats and intervention by Notopterygh rhizoma et radix - Yinghao Wang; Zhihuang Chen; Chen Liu; Xuehua Lu; Ce Yang; Songping Qiu (Taylor & Francis Group, 2019)
Context: Notopterygium incisum Ting ex H. T. Chang (Umbelliferae) (NI) specializes in treatment of upper limb rheumatoid arthritis (RA), but the exact mechanism is unclear. P2Xs are useful targets for inflammatory pain therapy. It led us to hypothesize that NI may preferentially act on particular P2Xs and these receptors may be unevenly distributed in the upper/lower limb. Objective: To investigate P2Xs distribution in the upper/lower limb and NI's targets in upper limb RA. Materials and methods: The SD rats were randomized into 11 groups of 10 animals each. Eight experimental groups were established by the injection of 0.1 mL FCA into the plantar surface of rat paw. Three control groups suffered the same volume of saline. The articular cavities were then taken on the seventh day to detect P2Xs expression. NI (3 g/kg) and prednisone (10 mg/kg) were respectively given by oral gavage once daily for 14 d. The swelling degree and P2Xs were evaluated individually. Results: In normal rats, the expressions of P2X3 and P2X6 in forelimb were markedly higher than that of in hind limb (P < 0.05). After induced by FCA, P2X1, P2X3, P2X4, P2X5 and P2X7 were increased significantly (P < 0.01). The biggest difference was P2X3. In NI treatment rats, swelling degree of the 7th/14th day in forelimb was 68.24%/38.89%, whereas that of in hind limb was 88.72%/79.92%. P2X3 mRNA and protein expression was significantly reduced as contrasted with the control group (P < 0.05). Conclusions: P2X3 receptor was predominantly expressed in the forelimb RA rat. NI relieved the FCA-induced RA by inhibiting upper limb's P2X3 receptor.